An unusual presentation of liver abscess secondary to toxoplasmosis in Nepal. (March 2022) - Adhikari, P.; Pahari, R.; Joshi, S.R.; Acharya, S.; Pant, S.
Abstract : Purpose: An unusual presentation of liver abscess secondary to toxoplasmosis in Nepal Methods & Materials: This is a case report on a case of liver abscess admitted in the hospital. Results: A 45-year old immunocompetent male presented to the emergency department with complaints of high-grade fever for ten days along with abdominal discomfort, anorexia, nausea and vomiting for 5 days. Clinically, he had fever, tachycardia, decreased breath sound on right chest & hepatomegaly. In labs, he had neutrophilic leukocytosis (22.7 K/microliter) and mildly elevated liver enzymes. The CT scan of chest, abdomen & pelvis reported hepatic abscess on the right lobe of liver (17.2 × 8.4 × 11.7 cm) which was drained under ultrasonography guidance. The patient was started empirically on IV antibiotics: Piperacillin-Tazobactam & Metronidazole. Blood, sputum & urine cultures were negative. The results of drained pus were negative for gram stain, culture, AFB stain, TB-PCR, fungal stain/culture, anaerobic culture, ova/parasites except for gram stain positive for possible trophozoites of Toxoplasma gondii, supported by strongly positive Toxoplasma IgG serology. The patient continued to have a fever. On further questioning, he mentioned cleaning the litter box of a postpartum cat weeks before he started having fever. On the fourth day of admission, oral Bactrim-DS(160 mg Trimethoprim and 800 mg Sulfamethoxazole) was added to the regimen, after which the patient became afebrile & clinically improved within 24 hours. The patient was discharged home on oral Bactrim-DS. There was complete resolution of liver abscess in ultrasonographic evaluation of the abdomen performed after 4 weeks, & oral antibiotic was stopped. Conclusion: This is the only case of liver abscess caused by toxoplasmosis, reported from Nepal. Liver abscess is commonly caused by Entamoeba histolytica or Enterobacteriaceae. However, Nepal being endemic to Toxoplasma, initial differential diagnosis should also include toxoplasmosis. As part of work up for toxoplasmosis, the abscess should be drained and histopathology sent for special stains (Hematoxylin & Eosin, Wright's or Giemsa), serum sent for serology, and abscess material sent for PCR if available.